Effect of Game-Based Learning on Grade 11 Senior High School Science Students' Learning Interest - Irfan, M; Sari Rahayu Rahman; Agus (Universitas Sulawesi Barat, 2024)
This study aimed to determine the effect of game-based learning on the learning interest of 11th-grade science students at a senior high school. This quantitative research employed a quasi-experimental design with a nonequivalent control group design. The sample consisted of 48 students divided into one control group and one experimental group, selected using cluster random sampling. The research was conducted at a senior high school in West Sulawesi with 11th-grade science students. Data was collected using a questionnaire. The results showed that there was a significant effect of game-based learning on students' learning interest in the reproductive system material for 11th-grade science students at a senior high school in West Sulawesi. This can be seen from the results of the hypothesis test using the Chi-Square Test, which obtained a significance value of 0.000. Since 0.000 < 0.05, it can be concluded that the game-based learning method has a significant effect on students' learning interest. This is consistent with the fact that the majority of students in the experimental class had a high category of learning interest, with a percentage of 70.8%. In learning using the game-based learning method, students were more enthusiastic about the learning process because in game-based learning, students competed to get the highest score or points, so they felt challenged to participate in every game. The game-based learning method is very suitable for application in classes where students like kinesthetic learning styles because it can influence learning interest which can impact student achievement.